Soixante-trois. La peur de la grande année climactérique à la Renaissance - Engammare, Max (Titre courant, 2013)
People have interpreted the numeration of the years of their life since Antiquity (when, for example, the Emperor Augustus did so). Ancient medical theories thus maintained that matter is renewed every seven or nine years. The product of these two numbers is sixty-three, and the sixty-third year of a person's life - the great climacteric - was believed to be very critical. Max Engammare presents the history of the anxiety surrounding this year that came back into force during the Renaissance, as early as Petrarch but especially with Marsilio Ficino. This book touches on most of the great names of the age, from Philipp Melanchthon and Theodore de Bèze to Rabelais. The question of the sixty-third king of France, Henri III or Henri IV, was also discussed by members of the League. The goal is to achieve an understanding of the arithmetic of these ancient fears that were reborn at the end of the 1400s and which have not in fact completely disappeared today-a proof of this is Sigmund Freud and the curse of 27 listing all the famous artists dead at the age of 27 (three times nine).